Physician Privacy Concerns when Disclosing Patient Data for Public Health Purposes During a Pandemic Influenza Outbreak - El Emam, Khaled (Université d'Ottawa | University of Ottawa, 2011)
Background: Privacy concerns by providers have been a barrier to disclosing patient information for public health purposes. This is the case even for mandated notifiable disease reporting. In the context of a pandemic it has been argued that the public good should supersede an individual’s right to privacy. The precise nature of these provider privacy concerns, and whether they are diluted in the context of a pandemic are not known. Our objective was to understand the privacy barriers which could potentially influence family physicians’ reporting of patient-level surveillance data to public health agencies during the Fall 2009 pandemic H1N1 influenza outbreak. Methods: Thirty seven family doctors participated in a series of five focus groups between October 29-31 2009. They also completed a survey about the data they were willing to disclose to public health units. Descriptive statistics were used to summarize the amount of patient detail the participants were willing to disclose, factors that would facilitate data disclosure, and the consensus on those factors. The analysis of the qualitative data was based on grounded theory. Results: The family doctors were reluctant to disclose patient data to public health units. This was due to concerns about the extent to which public health agencies are dependable to protect health information (trusting beliefs), and the possibility of loss due to disclosing health information (risk beliefs). We identified six specific actions that public health units can take which would affect these beliefs, and potentially increase the willingness to disclose patient information for public health purposes. Conclusions: The uncertainty surrounding a pandemic of a new strain of influenza has not changed the privacy concerns of physicians about disclosing patient data. It is important to address these concerns to ensure reliable reporting during future outbreaks.
Keywords: Privacy concerns; Pandemic; Disease reporting; H1N1 influenza outbreak; Trusting beliefs; Risk beliefs; Patient data